(untitled) - Stopford, Martin (London, 1988)
Now in its second edition, Maritime Economics provides a valuable introduction to the organization and workings of the global shipping industry. The author outlines the economic theory behind this large and complex subject as well as many of the operational practicalities involved...
Keywords: Merchant marine,Thương thuyền biển